Preparation method of wear-resistant and anti-fouling coating for porcelain insulator

CN122916729APending Publication Date: 2026-10-16JIANGXI PINGXIANG EAST CHINA EXPORT ELECTRIC PORCELAIN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611233679.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,随着电网规模持续扩大和运行环境日趋复杂,瓷绝缘子面临两大长期未能根本解决的技术难题:其一是风沙、扬尘等恶劣自然条件下,绝缘子表面釉层长期遭受固体颗粒冲刷,导致磨损老化、表面粗糙度增加,加速污秽累积;其二是表面污秽层在潮湿天气下受潮,形成导电膜,引发污秽闪络事故,严重威胁电网安全稳定运行

Benefits of technology

[0011]The beneficial effects of this invention are as follows: the surface coating of the porcelain insulator prepared by the method described in this invention has high Vickers hardness and pollution resistance, giving the porcelain insulator excellent wear resistance and pollution resistance, thus improving the durability of the porcelain insulator. Through comparison, this invention found that composite graphene oxide can significantly improve the surface hardness of the coating. This may be because graphene oxide can induce the precipitation of silica crystals during sintering, promoting the densification of the coating interior. Simultaneously, the precipitated silica crystals also have high hardness, thereby improving the overall surface hardness and wear resistance of the coating. By first modifying the composite particles with ethylenediamine hydrochloride through amination, the interaction between the composite particle surface and boric acid is improved. Subsequently, boric acid composite calcination forms a boron oxide coating. During sintering, the boron oxide coating layer easily combines with the inner titanium oxide layer to form a low-melting-temperature compound, improving the bonding between the particles and the inner layer, and simultaneously improving the density of the coating to a certain extent, achieving high densification, thereby improving the pollution resistance of the coating. In addition, this invention, by doping with a small amount of rare earth cerium, can also effectively improve the microstructure and enhance the coating performance. A dense titanium oxide matrix layer is first prepared, which acts as a buffer layer to alleviate thermal stress caused by the difference in thermal expansion coefficients between the outer coating and the ceramic insulator body, significantly improving the adhesion between the coating and the ceramic body and preventing coating peeling. The introduced manganese ions dispersed in the titanium oxide matrix can increase the hardness of the inner coating and improve its specific surface area, providing conditions for the subsequent coating of the outer layer. The additive powder prepared by ammonium molybdate contains metastable molybdenum oxide, which easily transforms into fine grains during high-temperature sintering, thereby improving the strength and hardness of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1786677640906-000001
    Figure REF-OBJ-1786677640906-000001
Patent Text Reader

Abstract

The application discloses a kind of porcelain insulator wear-resistant antifouling coating preparation method, comprising: (1) preparation composite particle;(2) composite particle is added in N, N-dimethylformamide, stirring dispersion, then add ethylenediamine hydrochloride, heat preservation, solid-liquid separation, washing, drying;Solid phase after drying is added in deionized water, water bath preservation, then add boric acid, fully stir, reduced pressure evaporation, calcination under protective atmosphere, obtain additive powder;(3) in the surface of porcelain insulator preparation obtains inner coating;(4) kaolin, quartz powder, additive powder, potassium feldspar, dolomite, zinc oxide powder, barium titanate powder, five sodium triphosphate hexahydrate, carboxymethyl cellulose are mixed uniformly to form mixed material, add water to prepare slurry, brush, air dry, heat sintering, obtain porcelain insulator wear-resistant antifouling coating.The porcelain insulator surface coating prepared by the application has higher vickers hardness and antifouling grade, so that the porcelain insulator has excellent wear resistance and antifouling performance, improves the durability of porcelain insulator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of insulator coating materials technology, and in particular to a method for preparing a wear-resistant and anti-fouling coating for porcelain insulators. Background Technology

[0002] Porcelain insulators are made of inorganic silicate materials through high-temperature sintering and serve as fundamental external insulation components in power transmission and transformation lines, providing both electrical insulation and mechanical fixation. Due to their excellent electromechanical properties and durability, porcelain insulators have long held a dominant position in the field of external insulation for power transmission and transformation lines. However, with the continuous expansion of the power grid and the increasingly complex operating environment, porcelain insulators face two long-standing and unresolved technical challenges: First, under harsh natural conditions such as wind, sand, and dust, the glaze layer on the insulator surface is subjected to long-term erosion by solid particles, leading to wear, aging, increased surface roughness, and accelerated accumulation of contaminants. Second, the surface contaminant layer becomes damp in humid weather, forming a conductive film that can trigger contamination flashover accidents, seriously threatening the safe and stable operation of the power grid. Summary of the Invention

[0003] Therefore, the present invention provides a method for preparing a wear-resistant and anti-fouling coating for porcelain insulators, comprising the following steps: (1) In a microwave reactor, ammonium molybdate and ethylenediamine are added to deionized water and stirred until homogeneous. Then, cerium chloride is added and stirred until homogeneous. Hydrochloric acid is added dropwise to adjust the pH to acidic. The reactor is then sealed and microwave-heated for reaction. After reaction, solid-liquid separation is performed, the solid phase is washed and dried. The dried solid phase is added to deionized water in the reactor and stirred to disperse. Then, L-cysteine ​​is added and stirred until homogeneous. After the addition is complete, graphene oxide solution is added. The reactor is then sealed, heated, and kept warm. After the warming is completed, the mixture is cooled to room temperature, solid-liquid separation is performed, the solid phase is washed and dried, and then calcined in a protective gas atmosphere to obtain composite particles. (2) The composite particles were added to N,N-dimethylformamide, stirred and dispersed, then ethylenediamine hydrochloride was added, and the mixture was heated in a water bath and kept warm. After the heat was maintained, the solid and liquid were separated, the solid phase was washed and dried. The dried solid phase was added to deionized water and stirred and mixed. The mixture was kept warm in a water bath, then boric acid was added. After the addition was made, the mixture was stirred thoroughly, and then the solvent was removed by vacuum evaporation. The mixture was then calcined under a protective atmosphere to obtain the additive powder. (3) Prepare an ethanol solution of tetrabutyl titanate and an aqueous solution of manganese nitrate; add ethanol to the aqueous solution of manganese nitrate, stir evenly, then add hydrochloric acid, stir and mix evenly, then add the ethanol solution of tetrabutyl titanate, stir evenly to form a coating solution; immerse the porcelain insulator in the coating solution to fully wet it, then take out the porcelain insulator, dry it, and calcine it to obtain the inner coating layer. (4) Kaolin, quartz powder, the additive powder, potassium feldspar, dolomite, zinc oxide powder, barium titanate powder, pentasodium triphosphate hexahydrate, and carboxymethyl cellulose are mixed to form a mixture. The mixture is added to water and stirred to form a slurry. The slurry is brushed onto the surface of the inner coating layer, then air-dried and heated to sinter to obtain the wear-resistant and anti-fouling coating of the porcelain insulator.

[0004] Further, the ratio of ammonium molybdate and ethylenediamine added to deionized water, followed by the addition of cerium chloride, is ammonium molybdate:ethylenediamine:cerium chloride:deionized water = 1.0–1.2 g: 0.6–0.8 g: 0.04–0.09 g: 15 mL; hydrochloric acid is added dropwise to adjust the pH to 4–5, wherein the concentration of the solute in the hydrochloric acid is 1 mol / L; the microwave heating reaction temperature is 130–140 °C, and the reaction time is 4–5 h.

[0005] Further, in step (1), the ratio of the dried solid phase added to deionized water in the reactor is 0.2-0.4 g: 20 mL for dried solid phase: deionized water. The ratio of the amount of L-cysteine ​​and graphene oxide solution added to the amount of dried solid phase added is 0.2-0.4 g: 1.1-1.3 g: 40-50 mL for dried solid phase: L-cysteine: graphene oxide solution = 0.2-0.4 g: 1.1-1.3 g: 40-50 mL for graphene oxide solution. The graphene oxide solution is a graphene oxide dispersion obtained by mixing graphene oxide with deionized water at a mass ratio of 4-5 mg: 1 mL. After sealing the reactor, the temperature is heated to 180-200°C and kept at that temperature for 12-15 hours. The calcination temperature is 730-750°C, the calcination time is 2-3 hours, and the protective gas is argon.

[0006] Further, in step (2), the composite particles are added to N,N-dimethylformamide, and the ratio of ethylenediamine hydrochloride added thereafter is composite particles: ethylenediamine hydrochloride: N,N-dimethylformamide = 0.2~0.4g: 4~5g: 100mL; the mixture is heated in a water bath to 90±2℃ and kept warm for more than 24 hours.

[0007] Further, in step (2), the dried solid phase is added to deionized water, and then the ratio of boric acid added is 2-3 g of dried solid phase: 0.4-0.6 g of deionized water: 20 mL. The water bath temperature is 80±5℃, and reflux is carried out during the heat preservation process. The calcination temperature under the protective atmosphere is 380-400℃, and the calcination time is 5-6 h. The protective atmosphere is a nitrogen atmosphere.

[0008] Further, in step (3), the ethanol solution of titanate n-butyl ester is prepared by adding 150-160 mL of titanate n-butyl ester to 500 mL of ethanol; the concentration of manganese nitrate in the aqueous solution of manganese nitrate is 10-15 g / 100 mL, and the solvent is water; the ratio of ethanol to titanate n-butyl ester ethanol solution added to the aqueous solution of manganese nitrate is aqueous solution of manganese nitrate: ethanol: titanate n-butyl ester ethanol solution = 10-15 mL: 200 mL: 500 mL; the concentration of solute in the hydrochloric acid is 1 mol / L, and the pH of the solution is adjusted to 2-3 by adding hydrochloric acid; the calcination temperature is 530-550℃, and the calcination time is 2-3 h.

[0009] Further, in step (4), the components are as follows by weight: 20-22 parts kaolin, 25-30 parts quartz powder, 10-15 parts additive powder, 6-9 parts potassium feldspar, 1-2 parts dolomite, 2-3 parts zinc oxide powder, 1-2 parts barium titanate powder, 0.15-0.2 parts pentasodium triphosphate hexahydrate, and 0.12-0.15 parts carboxymethyl cellulose.

[0010] Further, in step (4), the ratio of the mixture to water is 10g:30mL. The heating and sintering process is as follows: the temperature is raised to 1000℃ at a heating rate of 5℃ / min, and then held for 30min after each heating for 1 hour until it reaches 1000℃ and is held for 1 hour. Then the temperature is raised to 1100℃ at a heating rate of 2℃ / min, and held for 15-20min after reaching the temperature. Finally, the temperature is cooled to room temperature with the furnace.

[0011] The beneficial effects of this invention are as follows: the surface coating of the porcelain insulator prepared by the method described in this invention has high Vickers hardness and pollution resistance, giving the porcelain insulator excellent wear resistance and pollution resistance, thus improving the durability of the porcelain insulator. Through comparison, this invention found that composite graphene oxide can significantly improve the surface hardness of the coating. This may be because graphene oxide can induce the precipitation of silica crystals during sintering, promoting the densification of the coating interior. Simultaneously, the precipitated silica crystals also have high hardness, thereby improving the overall surface hardness and wear resistance of the coating. By first modifying the composite particles with ethylenediamine hydrochloride through amination, the interaction between the composite particle surface and boric acid is improved. Subsequently, boric acid composite calcination forms a boron oxide coating. During sintering, the boron oxide coating layer easily combines with the inner titanium oxide layer to form a low-melting-temperature compound, improving the bonding between the particles and the inner layer, and simultaneously improving the density of the coating to a certain extent, achieving high densification, thereby improving the pollution resistance of the coating. In addition, this invention, by doping with a small amount of rare earth cerium, can also effectively improve the microstructure and enhance the coating performance. A dense titanium oxide matrix layer is first prepared, which acts as a buffer layer to alleviate thermal stress caused by the difference in thermal expansion coefficients between the outer coating and the ceramic insulator body, significantly improving the adhesion between the coating and the ceramic body and preventing coating peeling. The introduced manganese ions dispersed in the titanium oxide matrix can increase the hardness of the inner coating and improve its specific surface area, providing conditions for the subsequent coating of the outer layer. The additive powder prepared by ammonium molybdate contains metastable molybdenum oxide, which easily transforms into fine grains during high-temperature sintering, thereby improving the strength and hardness of the coating. Detailed Implementation

[0012] The present invention will be further described below with reference to the embodiments.

[0013] Example 1

[0014] A method for preparing a wear-resistant and anti-fouling coating for porcelain insulators includes the following steps: (1) In a microwave reactor, ammonium molybdate and ethylenediamine were added to deionized water and stirred for 20 min to mix. Then, cerium chloride was added and stirred for another 20 min. The ratio of ammonium molybdate, ethylenediamine, and cerium chloride added to the deionized water was ammonium molybdate:ethylenediamine:cerium chloride:deionized water = 1.0 g:0.6 g:0.04 g:15 mL. Hydrochloric acid was added dropwise to adjust the pH to 4, and the concentration of the solute in the hydrochloric acid was 1 mol / L. The reactor was then sealed and microwave-heated at 140°C for 4 h. After the reaction, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80°C for 1 h. The dried solid phase was then added to deionized water in the reactor and stirred to disperse. The ratio of the dried solid phase added to deionized water was dried solid phase:deionized water = 0.4 g. g: 20mL, then add L-cysteine, continue stirring for 10min after the addition is complete, then add graphene oxide solution. The ratio of the amount of L-cysteine ​​and graphene oxide solution added to the amount of dried solid phase added is dried solid phase: L-cysteine: graphene oxide solution = 0.4g: 1.1g: 50mL, wherein the graphene oxide solution is a graphene oxide dispersion obtained by adding graphene oxide to deionized water at a mass ratio of graphene oxide: deionized water = 4mg: 1mL and stirring. Seal the reaction vessel, heat to 200℃ and keep warm for 12h. After the holding time is completed, cool to room temperature, separate the solid and liquid, wash the solid phase 3 times with deionized water, dry at 80℃ for 1h, and then calcine in an argon protective atmosphere. The calcination temperature is 730℃ and the calcination time is 3h to obtain composite particles. (2) The composite particles were added to N,N-dimethylformamide and stirred for 30 min to disperse them. Then, ethylenediamine hydrochloride was added. The ratio of composite particles to ethylenediamine hydrochloride added was 0.4 g: 4 g: 100 mL. The mixture was heated to 90 °C in a water bath and kept at that temperature for 24 h. After the heating period, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80 °C for 1 h. The dried solid phase was added to deionized water and stirred for 30 min. The mixture was then heated to 80 °C in a water bath and kept at that temperature. During the heating period, the mixture was refluxed. Boric acid was then added. The ratio of boric acid added was 2 g: 0.4 g: 20 mL. After the addition, the mixture was stirred at 80 °C for 8 h. The solvent was then removed by vacuum evaporation. The mixture was calcined under a nitrogen atmosphere at 380 °C for 6 h to obtain the additive powder. (3) Prepare an ethanol solution of tetrabutyl titanate and an aqueous solution of manganese nitrate; the ethanol solution of tetrabutyl titanate is prepared by adding 150 mL of tetrabutyl titanate to 500 mL of ethanol; the concentration of manganese nitrate in the aqueous solution of manganese nitrate is 15 g / 100 mL, and the solvent is water; add ethanol to the aqueous solution of manganese nitrate, stir for 20 min, then add hydrochloric acid, the concentration of solute in the hydrochloric acid is 1 mol / L, and adjust the pH of the solution to 2 by adding hydrochloric acid; stir for 30 min, mix well, and then add the ethanol solution of tetrabutyl titanate. The ratio of ethanol to ethanol in the aqueous solution of manganese nitrate is aqueous solution of manganese nitrate: ethanol: ethanol solution of tetrabutyl titanate = 10 mL: 200 mL: 500 mL; stir evenly to form a coating solution; immerse the porcelain insulator in the coating solution to fully wet it, then take out the porcelain insulator, dry it at 100℃ for 30 min, and calcine it at 550℃ for 2 h to obtain the inner coating layer. (4) Kaolin, quartz powder, the aforementioned additive powder, potassium feldspar, dolomite, zinc oxide powder, barium titanate powder, pentasodium triphosphate hexahydrate, and carboxymethyl cellulose are mixed to form a mixture. The components by weight are: 20 parts kaolin, 25 parts quartz powder, 10 parts the aforementioned additive powder, 6 parts potassium feldspar, 1 part dolomite, 2 parts zinc oxide powder, 1 part barium titanate powder, 0.15 parts pentasodium triphosphate hexahydrate, and 0.12 parts carboxymethyl cellulose. The mixture is added to water, and the ratio of the mixture to water is [missing information]. Material: Water = 10g: 30mL, stir for 40min to make a slurry, brush the slurry onto the surface of the inner coating, air dry for 2 days, and sinter in a nitrogen atmosphere to obtain the wear-resistant and anti-fouling coating of the porcelain insulator; the sintering process is as follows: heat up to 1000℃ at a heating rate of 5℃ / min, hold for 30min after each heating for 1 hour until 1000℃ is reached, hold for 1 hour, then heat up to 1100℃ at a heating rate of 2℃ / min, hold for 15min after reaching the temperature, and then cool to room temperature in the furnace.

[0015] Example 2

[0016] A method for preparing a wear-resistant and anti-fouling coating for porcelain insulators includes the following steps: (1) In a microwave reactor, ammonium molybdate and ethylenediamine were added to deionized water and stirred for 20 min to mix. Then, cerium chloride was added and stirred for another 20 min. The ratio of ammonium molybdate, ethylenediamine, and cerium chloride added to the deionized water was ammonium molybdate:ethylenediamine:cerium chloride:deionized water = 1.1 g:0.7 g:0.06 g:15 mL. Hydrochloric acid was added dropwise to adjust the pH to 4, and the concentration of the solute in the hydrochloric acid was 1 mol / L. The reactor was then sealed and microwave-heated at 140°C for 4 h. After the reaction, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80°C for 1 h. The dried solid phase was then added to deionized water in the reactor and stirred to disperse. The ratio of the dried solid phase added to deionized water was dried solid phase:deionized water = 0.4 g. The reaction vessel was prepared by adding 20 mL of L-cysteine ​​and stirring for 10 min. Then, graphene oxide solution was added. The ratio of the amount of L-cysteine ​​and graphene oxide solution added to the amount of dried solid phase added was 0.4 g: 1.2 g: 50 mL. The graphene oxide solution was a graphene dispersion obtained by mixing graphene oxide with deionized water at a mass ratio of 4 mg: 1 mL. The reaction vessel was sealed and heated to 200°C for 12 h. After heating, the mixture was cooled to room temperature, and the solid and liquid phases were separated. The solid phase was washed three times with deionized water, dried at 80°C for 1 h, and then calcined in an argon atmosphere at 730°C for 3 h to obtain composite particles. (2) The composite particles were added to N,N-dimethylformamide and stirred for 30 min to disperse them. Then, ethylenediamine hydrochloride was added. The ratio of composite particles to ethylenediamine hydrochloride added was 0.4 g: 4 g: 100 mL. The mixture was heated to 90 °C in a water bath and kept at that temperature for 24 h. After the heating period, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80 °C for 1 h. The dried solid phase was added to deionized water and stirred for 30 min. The mixture was then heated to 80 °C in a water bath and kept at that temperature. During the heating period, the mixture was refluxed. Boric acid was then added. The ratio of boric acid added was 2 g: 0.5 g: 20 mL. After the addition, the mixture was stirred at 80 °C for 8 h. The solvent was then removed by vacuum evaporation. The mixture was calcined under a nitrogen atmosphere at 380 °C for 6 h to obtain the additive powder. (3) Prepare an ethanol solution of tetrabutyl titanate and an aqueous solution of manganese nitrate; the ethanol solution of tetrabutyl titanate is prepared by adding 150 mL of tetrabutyl titanate to 500 mL of ethanol; the concentration of manganese nitrate in the aqueous solution of manganese nitrate is 15 g / 100 mL, and the solvent is water; add ethanol to the aqueous solution of manganese nitrate, stir for 20 min, then add hydrochloric acid, the concentration of solute in the hydrochloric acid is 1 mol / L, and adjust the pH of the solution to 2 by adding hydrochloric acid; stir for 30 min, mix well, and then add the ethanol solution of tetrabutyl titanate. The ratio of ethanol to ethanol in the aqueous solution of manganese nitrate is aqueous solution of manganese nitrate: ethanol: ethanol solution of tetrabutyl titanate = 10 mL: 200 mL: 500 mL; stir evenly to form a coating solution; immerse the porcelain insulator in the coating solution to fully wet it, then take out the porcelain insulator, dry it at 100℃ for 30 min, and calcine it at 550℃ for 2 h to obtain the inner coating layer. (4) Kaolin, quartz powder, the aforementioned additive powder, potassium feldspar, dolomite, zinc oxide powder, barium titanate powder, pentasodium triphosphate hexahydrate, and carboxymethyl cellulose are mixed to form a mixture. The components, by weight, are: 20 parts kaolin, 25 parts quartz powder, 10 parts the aforementioned additive powder, 7 parts potassium feldspar, 1 part dolomite, 2 parts zinc oxide powder, 1 part barium titanate powder, 0.18 parts pentasodium triphosphate hexahydrate, and 0.13 parts carboxymethyl cellulose. The mixture is added to water at a ratio of [missing information - likely a specific ratio]. Material: Water = 10g: 30mL, stir for 40min to make a slurry, brush the slurry onto the surface of the inner coating, air dry for 2 days, and sinter in a nitrogen atmosphere to obtain the wear-resistant and anti-fouling coating of the porcelain insulator; the sintering process is as follows: heat up to 1000℃ at a heating rate of 5℃ / min, hold for 30min after each heating for 1 hour until 1000℃ is reached, hold for 1 hour, then heat up to 1100℃ at a heating rate of 2℃ / min, hold for 15min after reaching the temperature, and then cool to room temperature in the furnace.

[0017] Example 3

[0018] A method for preparing a wear-resistant and anti-fouling coating for porcelain insulators includes the following steps: (1) In a microwave reactor, ammonium molybdate and ethylenediamine were added to deionized water and stirred for 20 min to mix. Then, cerium chloride was added and stirred for another 20 min. The ratio of ammonium molybdate, ethylenediamine, and cerium chloride added to the deionized water was ammonium molybdate:ethylenediamine:cerium chloride:deionized water = 1.1 g:0.7 g:0.08 g:15 mL. Hydrochloric acid was added dropwise to adjust the pH to 4, and the concentration of the solute in the hydrochloric acid was 1 mol / L. The reactor was then sealed and microwave-heated at 140°C for 4 h. After the reaction, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80°C for 1 h. The dried solid phase was then added to deionized water in the reactor and stirred to disperse. The ratio of the dried solid phase added to deionized water was dried solid phase:deionized water = 0.4 g. g: 20mL, then add L-cysteine, continue stirring for 10min after the addition is complete, then add graphene oxide solution. The ratio of the amount of L-cysteine ​​and graphene oxide solution added to the amount of dried solid phase added is dried solid phase: L-cysteine: graphene oxide solution = 0.4g: 1.2g: 50mL, wherein the graphene oxide solution is a graphene oxide dispersion obtained by adding graphene oxide to deionized water at a mass ratio of graphene oxide: deionized water = 4mg: 1mL and stirring. Seal the reaction vessel, heat to 200℃ and keep warm for 12h. After the holding time is completed, cool to room temperature, separate the solid and liquid, wash the solid phase 3 times with deionized water, dry at 80℃ for 1h, and then calcine in an argon protective atmosphere. The calcination temperature is 750℃ and the calcination time is 2h to obtain composite particles. (2) The composite particles were added to N,N-dimethylformamide and stirred for 30 min to disperse them. Then, ethylenediamine hydrochloride was added. The ratio of composite particles to ethylenediamine hydrochloride added was 0.4 g: 5 g: 100 mL. The mixture was heated to 90 °C in a water bath and kept at that temperature for 24 h. After the heating period, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80 °C for 1 h. The dried solid phase was added to deionized water and stirred for 30 min. The mixture was then heated to 80 °C in a water bath and kept at that temperature. During the heating period, the mixture was refluxed. Boric acid was then added. The ratio of boric acid added was 2 g: 0.5 g: 20 mL. After the addition, the mixture was kept at 80 °C and stirred for 8 h. The solvent was then removed by vacuum evaporation. The mixture was calcined under a nitrogen atmosphere at 400 °C for 5 h to obtain the additive powder. (3) Prepare an ethanol solution of tetrabutyl titanate and an aqueous solution of manganese nitrate; the ethanol solution of tetrabutyl titanate is prepared by adding 150 mL of tetrabutyl titanate to 500 mL of ethanol; the concentration of manganese nitrate in the aqueous solution of manganese nitrate is 10 g / 100 mL, and the solvent is water; add ethanol to the aqueous solution of manganese nitrate, stir for 20 min, then add hydrochloric acid, the concentration of solute in the hydrochloric acid is 1 mol / L, and adjust the pH of the solution to 2 by adding hydrochloric acid; stir for 30 min, mix well, and then add the ethanol solution of tetrabutyl titanate. The ratio of ethanol to ethanol in the aqueous solution of manganese nitrate is aqueous solution of manganese nitrate: ethanol: ethanol solution of tetrabutyl titanate = 15 mL: 200 mL: 500 mL; stir evenly to form a coating solution; immerse the porcelain insulator in the coating solution to fully wet it, then take out the porcelain insulator, dry it at 100°C for 30 min, and calcine it at 550°C for 2 h to obtain the inner coating layer. (4) Kaolin, quartz powder, the aforementioned additive powder, potassium feldspar, dolomite, zinc oxide powder, barium titanate powder, pentasodium triphosphate hexahydrate, and carboxymethyl cellulose are mixed to form a mixture. The components, by weight, are: 22 parts kaolin, 30 parts quartz powder, 15 parts the aforementioned additive powder, 8 parts potassium feldspar, 2 parts dolomite, 3 parts zinc oxide powder, 2 parts barium titanate powder, 0.18 parts pentasodium triphosphate hexahydrate, and 0.14 parts carboxymethyl cellulose. The mixture is added to water at a ratio of [missing information - likely a specific ratio]. Material: Water = 10g: 30mL, stir for 40min to make a slurry, brush the slurry onto the surface of the inner coating, air dry for 2 days, and sinter in a nitrogen atmosphere to obtain the wear-resistant and anti-fouling coating of the porcelain insulator; the sintering process is as follows: heat up to 1000℃ at a heating rate of 5℃ / min, hold for 30min after each heating for 1 hour until 1000℃ is reached, hold for 1 hour, then heat up to 1100℃ at a heating rate of 2℃ / min, hold for 15min after reaching the temperature, and then cool to room temperature in the furnace.

[0019] Example 4

[0020] A method for preparing a wear-resistant and anti-fouling coating for porcelain insulators includes the following steps: (1) In a microwave reactor, ammonium molybdate and ethylenediamine were added to deionized water and stirred for 20 min to mix. Then, cerium chloride was added and stirred for another 20 min. The ratio of ammonium molybdate, ethylenediamine, and cerium chloride added to the deionized water was ammonium molybdate:ethylenediamine:cerium chloride:deionized water = 1.2 g:0.8 g:0.09 g:15 mL. Hydrochloric acid was added dropwise to adjust the pH to 4, and the concentration of the solute in the hydrochloric acid was 1 mol / L. The reactor was then sealed and microwave-heated at 140°C for 4 h. After the reaction, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80°C for 1 h. The dried solid phase was then added to deionized water in the reactor and stirred to disperse. The ratio of the dried solid phase added to deionized water was dried solid phase:deionized water = 0.4 g. The reaction vessel was prepared by adding 20 mL of L-cysteine ​​and stirring for 10 min. Then, graphene oxide solution was added. The ratio of the amount of L-cysteine ​​and graphene oxide solution added to the amount of dried solid phase added was 0.4 g: 1.3 g: 50 mL. The graphene oxide solution was a graphene oxide dispersion obtained by mixing graphene oxide with deionized water at a mass ratio of 4 mg: 1 mL. The reaction vessel was sealed and heated to 200°C for 12 h. After heating, the mixture was cooled to room temperature, and the solid and liquid phases were separated. The solid phase was washed three times with deionized water, dried at 80°C for 1 h, and then calcined in an argon atmosphere at 750°C for 2 h to obtain composite particles. (2) The composite particles were added to N,N-dimethylformamide and stirred for 30 min to disperse them. Then, ethylenediamine hydrochloride was added. The ratio of composite particles to ethylenediamine hydrochloride added was 0.4 g: 5 g: 100 mL. The mixture was heated to 90 °C in a water bath and kept at that temperature for 24 h. After the heating period, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80 °C for 1 h. The dried solid phase was added to deionized water and stirred for 30 min. The mixture was then heated to 80 °C in a water bath and kept at that temperature. During the heating period, the mixture was refluxed. Boric acid was then added. The ratio of boric acid added was 2 g: 0.6 g: 20 mL. After the addition, the mixture was kept at 80 °C and stirred for 8 h. The solvent was then removed by vacuum evaporation. The mixture was calcined under a nitrogen atmosphere at 400 °C for 5 h to obtain the additive powder. (3) Prepare an ethanol solution of tetrabutyl titanate and an aqueous solution of manganese nitrate; the ethanol solution of tetrabutyl titanate is prepared by adding 150 mL of tetrabutyl titanate to 500 mL of ethanol; the concentration of manganese nitrate in the aqueous solution of manganese nitrate is 10 g / 100 mL, and the solvent is water; add ethanol to the aqueous solution of manganese nitrate, stir for 20 min, then add hydrochloric acid, the concentration of solute in the hydrochloric acid is 1 mol / L, and adjust the pH of the solution to 2 by adding hydrochloric acid; stir for 30 min, mix well, and then add the ethanol solution of tetrabutyl titanate. The ratio of ethanol to ethanol in the aqueous solution of manganese nitrate is aqueous solution of manganese nitrate: ethanol: ethanol solution of tetrabutyl titanate = 15 mL: 200 mL: 500 mL; stir evenly to form a coating solution; immerse the porcelain insulator in the coating solution to fully wet it, then take out the porcelain insulator, dry it at 100°C for 30 min, and calcine it at 550°C for 2 h to obtain the inner coating layer. (4) Kaolin, quartz powder, the aforementioned additive powder, potassium feldspar, dolomite, zinc oxide powder, barium titanate powder, pentasodium triphosphate hexahydrate, and carboxymethyl cellulose are mixed to form a mixture. The components, by weight, are: 22 parts kaolin, 30 parts quartz powder, 15 parts the aforementioned additive powder, 9 parts potassium feldspar, 2 parts dolomite, 3 parts zinc oxide powder, 2 parts barium titanate powder, 0.2 parts pentasodium triphosphate hexahydrate, and 0.15 parts carboxymethyl cellulose. The mixture is added to water, and the ratio of the mixture to water is [missing information]. Mix water = 10g : 30mL, stir for 40min to form a slurry, apply the slurry to the surface of the inner coating, air dry for 2 days, and sinter in a nitrogen atmosphere to obtain the wear-resistant and anti-fouling coating of the porcelain insulator; the sintering process is as follows: heat up to 1000℃ at a heating rate of 5℃ / min, hold for 30min after each heating for 1 hour until 1000℃ is reached, hold for 1 hour, then heat up to 1100℃ at a heating rate of 2℃ / min, hold for 15min after reaching the temperature, and then cool to room temperature in the furnace.

[0021] Comparative Example 1 A method for preparing a ceramic insulator coating as a comparison includes the following steps: (1) Ammonium molybdate and ethylenediamine were added to deionized water in a microwave reactor and stirred for 20 min to mix. Then cerium chloride was added and stirred for 20 min after adding the materials. The ratio of ammonium molybdate, ethylenediamine, cerium chloride, and deionized water to cerium chloride was ammonium molybdate: ethylenediamine: cerium chloride: deionized water = 1.1 g: 0.7 g: 0.08 g: 15 mL. Hydrochloric acid was added dropwise to adjust the pH to 4. The concentration of the solute in the hydrochloric acid was 1 mol / L. The reactor was then sealed and microwave-heated at 140 °C for 4 h. After the reaction, the solid and liquid phases were separated. The solid phase was washed three times with deionized water, dried at 80 °C for 1 h, and then calcined in an argon atmosphere at 750 °C for 2 h to obtain the composite particles of this comparative example. (2) The composite particles were added to N,N-dimethylformamide and stirred for 30 min to disperse them. Then, ethylenediamine hydrochloride was added. The ratio of composite particles to ethylenediamine hydrochloride added was 0.4 g: 5 g: 100 mL. The mixture was heated to 90 °C in a water bath and kept at that temperature for 24 h. After the heating period, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80 °C for 1 h. The dried solid phase was added to deionized water and stirred for 30 min. The mixture was then heated to 80 °C in a water bath and kept at that temperature. During the heating period, the mixture was refluxed. Boric acid was then added. The ratio of boric acid added was 2 g: 0.5 g: 20 mL. After the addition, the mixture was kept at 80 °C and stirred for 8 h. The solvent was then removed by vacuum evaporation. The mixture was calcined under a nitrogen atmosphere at 400 °C for 5 h to obtain the additive powder. (3) Prepare an ethanol solution of tetrabutyl titanate and an aqueous solution of manganese nitrate; the ethanol solution of tetrabutyl titanate is prepared by adding 150 mL of tetrabutyl titanate to 500 mL of ethanol; the concentration of manganese nitrate in the aqueous solution of manganese nitrate is 10 g / 100 mL, and the solvent is water; add ethanol to the aqueous solution of manganese nitrate, stir for 20 min, then add hydrochloric acid, the concentration of solute in the hydrochloric acid is 1 mol / L, and adjust the pH of the solution to 2 by adding hydrochloric acid; stir for 30 min, mix well, and then add the ethanol solution of tetrabutyl titanate. The ratio of ethanol to ethanol in the aqueous solution of manganese nitrate is aqueous solution of manganese nitrate: ethanol: ethanol solution of tetrabutyl titanate = 15 mL: 200 mL: 500 mL; stir evenly to form a coating solution; immerse the porcelain insulator in the coating solution to fully wet it, then take out the porcelain insulator, dry it at 100°C for 30 min, and calcine it at 550°C for 2 h to obtain the inner coating layer. (4) Kaolin, quartz powder, the aforementioned additive powder, potassium feldspar, dolomite, zinc oxide powder, barium titanate powder, pentasodium triphosphate hexahydrate, and carboxymethyl cellulose are mixed to form a mixture. The components, by weight, are: 22 parts kaolin, 30 parts quartz powder, 15 parts the aforementioned additive powder, 8 parts potassium feldspar, 2 parts dolomite, 3 parts zinc oxide powder, 2 parts barium titanate powder, 0.18 parts pentasodium triphosphate hexahydrate, and 0.14 parts carboxymethyl cellulose. The mixture is added to water at a ratio of [missing information - likely a specific ratio]. Material: Water = 10g: 30mL, stir for 40min to make a slurry, brush the slurry onto the surface of the inner coating, air dry for 2 days, heat and sinter in a nitrogen atmosphere to obtain the porcelain insulator coating of this comparative example; the sintering process is as follows: heat up to 1000℃ at a heating rate of 5℃ / min, hold for 30min after each heating for 1 hour until 1000℃ is reached and hold for 1 hour, then heat up to 1100℃ at a heating rate of 2℃ / min, hold for 15min after reaching the temperature, and then cool to room temperature in the furnace.

[0022] Comparative Example 2 A method for preparing a ceramic insulator coating as a comparison includes the following steps: (1) In a microwave reactor, ammonium molybdate and ethylenediamine were added to deionized water and stirred for 20 min to mix. Then, cerium chloride was added and stirred for another 20 min. The ratio of ammonium molybdate, ethylenediamine, and cerium chloride added to the deionized water was ammonium molybdate:ethylenediamine:cerium chloride:deionized water = 1.1 g:0.7 g:0.08 g:15 mL. Hydrochloric acid was added dropwise to adjust the pH to 4, and the concentration of the solute in the hydrochloric acid was 1 mol / L. The reactor was then sealed and microwave-heated at 140°C for 4 h. After the reaction, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80°C for 1 h. The dried solid phase was then added to deionized water in the reactor and stirred to disperse. The ratio of the dried solid phase added to deionized water was dried solid phase:deionized water = 0.4 g. g: 20mL, then add L-cysteine, continue stirring for 10min after the addition is complete, then add graphene oxide solution. The ratio of the amount of L-cysteine ​​and graphene oxide solution added to the amount of dried solid phase added is dried solid phase: L-cysteine: graphene oxide solution = 0.4g: 1.2g: 50mL, wherein the graphene oxide solution is a graphene oxide dispersion obtained by adding graphene oxide to deionized water at a mass ratio of graphene oxide: deionized water = 4mg: 1mL and stirring. Seal the reaction vessel, heat to 200℃ and keep warm for 12h. After the holding time is completed, cool to room temperature, separate the solid and liquid, wash the solid phase 3 times with deionized water, dry at 80℃ for 1h, and then calcine in an argon protective atmosphere. The calcination temperature is 750℃ and the calcination time is 2h to obtain composite particles. (2) The composite particles were added to N,N-dimethylformamide and stirred for 30 min to disperse them. Then, ethylenediamine hydrochloride was added. The ratio of the composite particles to N,N-dimethylformamide added was composite particles: ethylenediamine hydrochloride: N,N-dimethylformamide = 0.4 g: 5 g: 100 mL. The mixture was heated to 90 °C in a water bath and kept warm for 24 h. After the warming process, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80 °C for 1 h to obtain the additive powder of this comparative example. (3) Prepare an ethanol solution of tetrabutyl titanate and an aqueous solution of manganese nitrate; the ethanol solution of tetrabutyl titanate is prepared by adding 150 mL of tetrabutyl titanate to 500 mL of ethanol; the concentration of manganese nitrate in the aqueous solution of manganese nitrate is 10 g / 100 mL, and the solvent is water; add ethanol to the aqueous solution of manganese nitrate, stir for 20 min, then add hydrochloric acid, the concentration of solute in the hydrochloric acid is 1 mol / L, and adjust the pH of the solution to 2 by adding hydrochloric acid; stir for 30 min, mix well, and then add the ethanol solution of tetrabutyl titanate. The ratio of ethanol to ethanol in the aqueous solution of manganese nitrate is aqueous solution of manganese nitrate: ethanol: ethanol solution of tetrabutyl titanate = 15 mL: 200 mL: 500 mL; stir evenly to form a coating solution; immerse the porcelain insulator in the coating solution to fully wet it, then take out the porcelain insulator, dry it at 100°C for 30 min, and calcine it at 550°C for 2 h to obtain the inner coating layer. (4) Kaolin, quartz powder, the aforementioned additive powder, potassium feldspar, dolomite, zinc oxide powder, barium titanate powder, pentasodium triphosphate hexahydrate, and carboxymethyl cellulose are mixed to form a mixture. The components, by weight, are: 22 parts kaolin, 30 parts quartz powder, 15 parts the aforementioned additive powder, 8 parts potassium feldspar, 2 parts dolomite, 3 parts zinc oxide powder, 2 parts barium titanate powder, 0.18 parts pentasodium triphosphate hexahydrate, and 0.14 parts carboxymethyl cellulose. The mixture is added to water at a ratio of [missing information - likely a specific ratio]. Material: Water = 10g: 30mL, stir for 40min to make a slurry, brush the slurry onto the surface of the inner coating, air dry for 2 days, heat and sinter in a nitrogen atmosphere to obtain the porcelain insulator coating of this comparative example; the sintering process is as follows: heat up to 1000℃ at a heating rate of 5℃ / min, hold for 30min after each heating for 1 hour until 1000℃ is reached and hold for 1 hour, then heat up to 1100℃ at a heating rate of 2℃ / min, hold for 15min after reaching the temperature, and then cool to room temperature in the furnace.

[0023] Comparative Example 3 A method for preparing a ceramic insulator coating as a comparison includes the following steps: (1) In a microwave reactor, ammonium molybdate and ethylenediamine were added to deionized water and stirred for 20 min to mix. Then, cerium chloride was added and stirred for another 20 min. The ratio of ammonium molybdate, ethylenediamine, and cerium chloride added to the deionized water was ammonium molybdate:ethylenediamine:cerium chloride:deionized water = 1.1 g:0.7 g:0.08 g:15 mL. Hydrochloric acid was added dropwise to adjust the pH to 4, and the concentration of the solute in the hydrochloric acid was 1 mol / L. The reactor was then sealed and microwave-heated at 140°C for 4 h. After the reaction, the solid and liquid phases were separated. The solid phase was washed three times with deionized water and dried at 80°C for 1 h. The dried solid phase was then added to deionized water in the reactor and stirred to disperse. The ratio of the dried solid phase added to deionized water was dried solid phase:deionized water = 0.4 g. g: 20mL, then add L-cysteine, continue stirring for 10min after the addition is complete, then add graphene oxide solution. The ratio of the amount of L-cysteine ​​and graphene oxide solution added to the amount of dried solid phase added is dried solid phase: L-cysteine: graphene oxide solution = 0.4g: 1.2g: 50mL, wherein the graphene oxide solution is a graphene oxide dispersion obtained by adding graphene oxide to deionized water at a mass ratio of graphene oxide: deionized water = 4mg: 1mL and stirring. Seal the reaction vessel, heat to 200℃ and keep warm for 12h. After the holding time is completed, cool to room temperature, separate the solid and liquid, wash the solid phase 3 times with deionized water, dry at 80℃ for 1h, and then calcine in an argon protective atmosphere. The calcination temperature is 750℃ and the calcination time is 2h to obtain composite particles. (2) Add the composite particles to deionized water and stir for 30 min. Heat the water bath to 80°C and keep it warm. During the warming process, condense and reflux. Then add boric acid. The ratio of composite particles to boric acid is 2 g: 0.5 g: 20 mL. After adding the materials, keep the water at 80°C and stir for 8 h. Then evaporate the solvent under reduced pressure and calcine under a nitrogen atmosphere at a temperature of 400°C for 5 h to obtain the additive powder. (3) Prepare an ethanol solution of tetrabutyl titanate and an aqueous solution of manganese nitrate; the ethanol solution of tetrabutyl titanate is prepared by adding 150 mL of tetrabutyl titanate to 500 mL of ethanol; the concentration of manganese nitrate in the aqueous solution of manganese nitrate is 10 g / 100 mL, and the solvent is water; add ethanol to the aqueous solution of manganese nitrate, stir for 20 min, then add hydrochloric acid, the concentration of solute in the hydrochloric acid is 1 mol / L, and adjust the pH of the solution to 2 by adding hydrochloric acid; stir for 30 min, mix well, and then add the ethanol solution of tetrabutyl titanate. The ratio of ethanol to ethanol in the aqueous solution of manganese nitrate is aqueous solution of manganese nitrate: ethanol: ethanol solution of tetrabutyl titanate = 15 mL: 200 mL: 500 mL; stir evenly to form a coating solution; immerse the porcelain insulator in the coating solution to fully wet it, then take out the porcelain insulator, dry it at 100°C for 30 min, and calcine it at 550°C for 2 h to obtain the inner coating layer. (4) Kaolin, quartz powder, the aforementioned additive powder, potassium feldspar, dolomite, zinc oxide powder, barium titanate powder, pentasodium triphosphate hexahydrate, and carboxymethyl cellulose are mixed to form a mixture. The components, by weight, are: 22 parts kaolin, 30 parts quartz powder, 15 parts the aforementioned additive powder, 8 parts potassium feldspar, 2 parts dolomite, 3 parts zinc oxide powder, 2 parts barium titanate powder, 0.18 parts pentasodium triphosphate hexahydrate, and 0.14 parts carboxymethyl cellulose. The mixture is added to water at a ratio of [missing information - likely a specific ratio]. Material: Water = 10g: 30mL, stir for 40min to make a slurry, brush the slurry onto the surface of the inner coating, air dry for 2 days, heat and sinter in a nitrogen atmosphere to obtain the porcelain insulator coating of this comparative example; the sintering process is as follows: heat up to 1000℃ at a heating rate of 5℃ / min, hold for 30min after each heating for 1 hour until 1000℃ is reached and hold for 1 hour, then heat up to 1100℃ at a heating rate of 2℃ / min, hold for 15min after reaching the temperature, and then cool to room temperature in the furnace.

[0024] Example 5

[0025] The microhardness of the ceramic insulator coatings prepared by the methods described in the above embodiments and comparative examples was tested using a Vickers hardness tester. The pressure was set to 0.3 kg and held for 15 s. Five points were tested for each sample and the average value was taken. The pollution resistance level of the ceramic insulator coatings prepared by the methods described in the above embodiments and comparative examples was tested according to the requirements of standard GB / T3810.14-2016. The results are shown in Table 1.

[0026] As shown in Table 1, the surface coating of the porcelain insulator prepared by the method described in this invention has high Vickers hardness and pollution resistance, resulting in excellent wear resistance and pollution resistance, thus improving the durability of the porcelain insulator. Through comparison, this invention found that composite graphene oxide significantly improves the surface hardness of the coating. This may be because graphene oxide can induce the precipitation of silica crystals during sintering, promoting densification within the coating. Simultaneously, the precipitated silica crystals also have high hardness, thereby improving the overall surface hardness and wear resistance of the coating. By first modifying the composite particles with ethylenediamine hydrochloride through amination, the interaction between the composite particle surface and boric acid is enhanced. Subsequently, boric acid composite calcination forms a boron oxide coating. During sintering, the boron oxide coating layer easily combines with the inner titanium oxide layer to form a low-melting-temperature compound, improving the bonding between the particles and the inner layer, and simultaneously improving the coating density to a certain extent, achieving high densification and thus improving the coating's pollution resistance. Furthermore, this invention, by doping with a small amount of rare earth cerium, can also effectively improve the microstructure and enhance the coating performance. A dense titanium oxide matrix layer is first prepared, which acts as a buffer layer to alleviate thermal stress caused by the difference in thermal expansion coefficients between the outer coating and the ceramic insulator body, significantly improving the adhesion between the coating and the ceramic body and preventing coating peeling. The introduced manganese ions dispersed in the titanium oxide matrix can increase the hardness of the inner coating and improve its specific surface area, providing conditions for the subsequent coating of the outer layer. The additive powder prepared by ammonium molybdate contains metastable molybdenum oxide, which easily transforms into fine grains during high-temperature sintering, thereby improving the strength and hardness of the coating.

[0027] Table 1

[0028] The technical solutions provided by the present invention have been described in detail above. For those skilled in the art, there will be changes in specific implementation methods and application scope based on the ideas of the embodiments of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A method for preparing a wear-resistant and anti-fouling coating for porcelain insulators, characterized in that, It includes the following steps: (1) In a microwave reactor, ammonium molybdate and ethylenediamine are added to deionized water and stirred until homogeneous. Then, cerium chloride is added and stirred until homogeneous. Hydrochloric acid is added dropwise to adjust the pH to acidic. The reactor is then sealed and microwave-heated for reaction. After reaction, solid-liquid separation is performed, the solid phase is washed and dried. The dried solid phase is added to deionized water in the reactor and stirred to disperse. Then, L-cysteine ​​is added and stirred until homogeneous. After the addition is complete, graphene oxide solution is added. The reactor is then sealed, heated, and kept warm. After the warming is completed, the mixture is cooled to room temperature, solid-liquid separation is performed, the solid phase is washed and dried, and then calcined in a protective gas atmosphere to obtain composite particles. (2) The composite particles were added to N,N-dimethylformamide, stirred and dispersed, then ethylenediamine hydrochloride was added, and the mixture was heated in a water bath and kept warm. After the heat was maintained, the solid and liquid were separated, the solid phase was washed and dried. The dried solid phase was added to deionized water and stirred and mixed. The mixture was kept warm in a water bath, then boric acid was added. After the addition was made, the mixture was stirred thoroughly, and then the solvent was removed by vacuum evaporation. The mixture was then calcined under a protective atmosphere to obtain the additive powder. (3) Prepare an ethanol solution of tetrabutyl titanate and an aqueous solution of manganese nitrate; add ethanol to the aqueous solution of manganese nitrate, stir evenly, then add hydrochloric acid, stir and mix evenly, then add the ethanol solution of tetrabutyl titanate, stir evenly to form a coating solution; immerse the porcelain insulator in the coating solution to fully wet it, then take out the porcelain insulator, dry it, and calcine it to obtain the inner coating layer. (4) Kaolin, quartz powder, the additive powder, potassium feldspar, dolomite, zinc oxide powder, barium titanate powder, pentasodium triphosphate hexahydrate, and carboxymethyl cellulose are mixed to form a mixture. The mixture is added to water and stirred to form a slurry. The slurry is brushed onto the surface of the inner coating layer, then air-dried and heated to sinter to obtain the wear-resistant and anti-fouling coating of the porcelain insulator.

2. The method for preparing a wear-resistant and anti-fouling coating for porcelain insulators according to claim 1, characterized in that, The ratio of ammonium molybdate and ethylenediamine to cerium chloride is ammonium molybdate:ethylenediamine:cerium chloride:deionized water = 1.0–1.2 g: 0.6–0.8 g: 0.04–0.09 g: 15 mL. Hydrochloric acid is added dropwise to adjust the pH to 4–5, and the concentration of the solute in the hydrochloric acid is 1 mol / L. The microwave heating reaction temperature is 130–140 °C, and the reaction time is 4–5 h.

3. The method for preparing a wear-resistant and anti-fouling coating for porcelain insulators according to claim 1, characterized in that, In step (1), the ratio of the dried solid phase added to deionized water in the reactor is 0.2-0.4 g: 20 mL. The ratio of the amount of L-cysteine ​​and graphene oxide solution added to the amount of dried solid phase is 0.2-0.4 g: 1.1-1.3 g: 40-50 mL. The graphene oxide solution is a graphene oxide dispersion obtained by mixing graphene oxide with deionized water at a mass ratio of 4-5 mg: 1 mL. After sealing the reactor, the temperature is raised to 180-200°C and kept at that temperature for 12-15 hours. The calcination temperature is 730-750°C, the calcination time is 2-3 hours, and the protective gas is argon.

4. The method for preparing a wear-resistant and anti-fouling coating for porcelain insulators according to claim 1, characterized in that, In step (2), the composite particles are added to N,N-dimethylformamide, and the ratio of ethylenediamine hydrochloride added thereafter is composite particles: ethylenediamine hydrochloride: N,N-dimethylformamide = 0.2-0.4g: 4-5g: 100mL; the mixture is heated in a water bath to 90±2℃ and kept warm for more than 24 hours.

5. The method for preparing a wear-resistant and anti-fouling coating for porcelain insulators according to claim 1, characterized in that, In step (2), the dried solid phase is added to deionized water, and then boric acid is added in the following ratio: dried solid phase: boric acid: deionized water = 2-3g: 0.4-0.6g: 20mL. The water bath temperature is 80±5℃, and reflux is carried out during the heat preservation process. The calcination temperature under the protective atmosphere is 380-400℃, and the calcination time is 5-6h. The protective atmosphere is a nitrogen atmosphere.

6. The method for preparing a wear-resistant and anti-fouling coating for porcelain insulators according to claim 1, characterized in that, In step (3), the ethanol solution of titanate is prepared by adding 150-160 mL of titanate to 500 mL of ethanol; the concentration of manganese nitrate in the aqueous solution of manganese nitrate is 10-15 g / 100 mL, and the solvent is water; the ratio of ethanol to titanate ethanol solution added to the aqueous solution of manganese nitrate is manganese nitrate aqueous solution: ethanol: titanate ethanol solution = 10-15 mL: 200 mL: 500 mL; the concentration of solute in the hydrochloric acid is 1 mol / L, and the pH of the solution is adjusted to 2-3 by adding hydrochloric acid; the calcination temperature is 530-550℃, and the calcination time is 2-3 h.

7. The method for preparing a wear-resistant and anti-fouling coating for porcelain insulators according to claim 1, characterized in that, In step (4), the components are as follows by weight: 20-22 parts kaolin, 25-30 parts quartz powder, 10-15 parts additive powder, 6-9 parts potassium feldspar, 1-2 parts dolomite, 2-3 parts zinc oxide powder, 1-2 parts barium titanate powder, 0.15-0.2 parts pentasodium triphosphate hexahydrate, and 0.12-0.15 parts carboxymethyl cellulose.

8. The method for preparing a wear-resistant and anti-fouling coating for porcelain insulators according to claim 1, characterized in that, In step (4), the ratio of the mixture to water is 10g:30mL. The heating and sintering process is as follows: the temperature is raised to 1000℃ at a rate of 5℃ / min, and then held for 30min after each 1h increase until it reaches 1000℃ and is held for 1h. Then the temperature is raised to 1100℃ at a rate of 2℃ / min, and held for 15-20min after reaching the temperature. Finally, the temperature is cooled to room temperature with the furnace.